PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN TOKO BUKU TOGA MAS SEMARANG - Riska Arisandi; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2017)
Business development requires companies to survive in the competition. Companies are more required to provide the optimal quality of services provided to consumers to create satisfaction so that consumers are loyal to the company. In addition, good pricing can also increase customer satisfaction. Toga Mas Book Store which is a retail company is required to be able to apply it. The purpose of this study is to know the effect of service quality and price on customer loyalty through customer satisfaction Bookstore Toga Mas Semarang. This type of research is explanatory research. Sampling technique used in this study is purposive sampling amounted to 100 people. This research uses quantitative analysis technique. Analytical methods used are correlation coefficient test, coefficient of determination, simple linear regression, multiple linear regression, t test, F test and test of sobel with SPSS program version 16. Based on the analysis, service quality and price have influence to customer loyalty through customer satisfaction. Quality of service and price have contribution influence to customer satisfaction variable equal to 29,2% where service quality have contribution 20,2% and price have contribution 28,7%. Quality of service and price have contribution influence to customer loyalty variable equal to 47,6% where service quality have contribution 38,6% and price have contribution 43,9%. Quality of service and price together have significant effect to customer satisfaction and customer loyalty . The conclusion of this study indicates that the quality of service and price partially or simultaneously affect customer satisfaction and customer loyalty bookstore Toga Mas Semarang Smartphone. Based on these results, suggestions for the Toga Mas bookstore must be to improve the quality of service and maintain a pricing strategy.